GENERALIZED MODEL OF THE ACTUAL WORK OF DECIDOUS AND CONIFEROUS WOOD UNDER AXIAL COMPRESSION ALONG THE FIBERS (Collection of scientific works «Modern structures of metal and wood», 2025)
Modern methods for determining the initial modulus of elasticity of solid wood are analyzed. The article presents the results of experimental and theoretical research on the selection of values  of  the  initial  modulus  of  elasticity  of  solid  wood  for  determining  the  theoretical  bearing capacity  of  bending  unreinforced  and  reinforced  elements  made  of  glued  laminated  timber.  The purpose of the work is to determine the features of determining the modulus of elasticity of wood and the reliability of determining the theoretical bearing capacity of bending elements made of wood using the deformation method. It is established that the closest results are the results of calculating the  theoretical  bearing  capacity  of  bending  elements  made  of  glued  laminated  timber  to  the experimental ones using a deformation model, which uses the initial modulus of elasticity established on the basis of solid wood from which the structure is made. The deformation model for calculating bending elements made of glued laminated timber involves the use of determined normal stresses based on deformations that have arisen in the normal cross-section of the bending element under external  loading.  The  stresses  in  the  calculated normal  cross-section  are  described  by  different functions in three different sections of the cross-section height. The first section is the tension section, starting from the bottom of the element to the neutral line and described by a linear function; the second  section  is  the  compression  section,  from  the  neutral  line  to  the  maximum  value  of  the compressive stresses is described by a nonlinear function; the third section is also a compression section, from the end of second section to the top of the bending element is described by a nonlinear function taking into account the appearance of a fold.
Keywords: wood; bending elemen; deformation mode; modulus of elasticity; earing capacity